The effects of presentation format on multiple document notetaking. (October 2018) - Van Meter, Peggy N.; Cameron, Chelsea
Highlights: Results indicate that verbal and visual documents are processed differently. Learners either took notes on only verbal presentation formats or took notes on all available documents. These data suggest that both verbal and visual documents can stimulate affective responses. This effect appears dependent on the particular contents for verbal documents, but is more uniform with visual documents. The more affective notes taken during study, the greater the number of affective questions produced on a post-reading task.